ON THE NECESSITY OF DISPOSAL AND REUSE OF LED LIGHT SOURCE MATERIALS AFTER THEIR END OF USE - Basova, Yuliia; Baghirov, Sabir; Kyslytsia, Svitlana; Huba, Liudmyla (Sworld-Us Conference proceedings, 2025)
The paper considers the problems of recycling and reuse of materials of LED light sources after the end of their service life. The emphasis is on the importance of the transition to a circular economy and eco-design as means of sustainable development. Th